PCSK9 Inhibitors in Real-world Practice: Analysis of Data from 314 Patients and 2 Years of Experience in a Center of Preventive Cardiology - Altschmiedová, Tereza; Todorovová, Veronika; Šnejdrlová, Michaela; Šatný, Martin; Češka, Richard (Current atherosclerosis reports, 2022)
PURPOSE OF REVIEW: PCSK9 inhibitors have been shown to be the most effective class of drugs modifying the levels of LDL-cholesterol as the main risk factor for atherosclerotic cardiovascular disease. The aim of this paper is to assess the effect of monoclonal antibodies on lipid and lipoprotein metabolism in real-world practice. RECENT FINDINGS: The outcome trials showed effective reduction of LDL-C by 56-62%. Landmark studies enrolling over a total of 46,000 patients with CHD in their medical history demonstrated the beneficial effect of both agents on cardiovascular morbidity and mortality. The data from real everyday clinical practice are very limited or missing. Even in real-world practice, PCSK9 inhibitors have been shown to be an effective, safe, and well-tolerated class of drugs with effects comparable with those reported from large randomized controlled trials.
Keywords: Alirocumab; Atherosclerotic cardiovascular disease (ASCVD); anticholesteremika; PCSK9 inhibitors; Real-world data (RWD); lidé; Anticholesteremic Agents; PCSK9 inhibitory; Cardiovascular Diseases; Evolocumab; Proprotein Convertase 9; kardiologie; Cardiology; PCSK9 Inhibitors; proproteinkonvertasa subtilisin/kexin typu 9; kardiovaskulární nemoci; LDL cholesterol; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Humans